Orthodontics and COVID-19 pandemic - a review - Aurelia Magdalena Enache; Dana Festila (Amaltea Medical Publishing House, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly infectious disease with a major impact on orthodontic practice regarding the risk of control transmission of COVID 19. Due to the particularities of orthodontic treatment which includes return-visits of the patients for a long period of time, the number of patients per day, dental aerosols-generated procedures risk, management considerations should be constant in order to update practice to the scientific evidence. The aim of this critical narrative review of the literature is to highlights the latest scientific data in order to control the transmission of SARS-CoV-2 infection in the orthodontic practice.